2002
DOI: 10.1038/sj.ijo.0802020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the β2-adrenergic receptor Arg16Gly polymorphism on longitudinal changes in obesity from childhood through young adulthood in a biracial cohort: the Bogalusa Heart Study

Abstract: BACKGROUND:The b2-adrenergic receptor (ADRB2) plays a major role in regulating energy expenditure by stimulating lipid metabolism in human adipose tissue. Polymorphisms in the ADRB2 gene have been associated with obesity and various weightrelated traits in cross-sectional studies of adults, but little is known about the effects of the ADRB2 gene on childhood obesity or the propensity to gain weight over time. OBJECTIVE: To assess the effects of a polymorphism in codon 16 (Arg16?Gly) of the ADRB2 gene, which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 31 publications
(25 reference statements)
1
42
0
2
Order By: Relevance
“…Polymorphisms located within β2-adrenergic receptor have been associ- ated with obesity in various ethnic groups [31]. One mutation known to decrease receptor density and efficiency is Arg16Gly, which is associated with longitudinal increases in weight gain in a large cohort of male children [32]. In other studies, the same mutation has been associated with a greater relative risk for developing Type 2 diabetes [33].…”
Section: Discussionmentioning
confidence: 92%
“…Polymorphisms located within β2-adrenergic receptor have been associ- ated with obesity in various ethnic groups [31]. One mutation known to decrease receptor density and efficiency is Arg16Gly, which is associated with longitudinal increases in weight gain in a large cohort of male children [32]. In other studies, the same mutation has been associated with a greater relative risk for developing Type 2 diabetes [33].…”
Section: Discussionmentioning
confidence: 92%
“…Two of these studies have examined weight gain in which weight was measured only twice (for example, van Rossum et al 33,34 ). Three studies have examined candidate gene associations with weight gain in longitudinal studies with adiposity measured over several years, 9,35,36 all of which focus on b-adrenergic receptors. The Bogalusa Heart study 9 has found suggestive evidence for increased weight gain from childhood to young adulthood in male carriers of the Gly allele of the ADRB2 Arg16Gly polymorphism, and this increase in weight gain is potentially dependent on b1-adrenergic receptor genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study investigated the relationship between a candidate gene and longitudinal changes in adiposity from childhood to young adulthood. 9 However, this study did not include measures of central obesity, focused on just a single polymorphism and did not examine potential interactions with environmental determinants of obesity such as socioeconomic status (SES).…”
Section: Introductionmentioning
confidence: 99%
“…Several of these failed to identify any association [3][4][5][6][7][8][9]. Other studies have found significant associations [8,10,11], but without a consensus regarding which allele is associated with obesity or related traits.…”
Section: Introductionmentioning
confidence: 99%